Higher knee joint work is a risk factor for patellar tendinopathy in male volleyball players: A prospective study - Bleecker, C. D.; Vermeulen, S.; Willems, T.; Spanhove, V.; Segers, V.; Steyaert, A.; Roosen, P.; Vanrenterghem, J.; Ridder, R. D. (Journal of Sports Sciences, 2025)
This study aimed to prospectively investigate knee jump-landing biomechanics associated as risk factors for patellar tendinopathy (PT) in volleyball players. Seventy-nine healthy male volleyball players were followed during one season. Pre-season, three-dimensional full-body biomechanics were collected during spike jump, block jump and drop vertical jump. During follow-up, injury data were collected by using a weekly and 3-monthly online retrospective control questionnaire. Univariate cox regression with competing risk analysis was used to identify contributors to the development of PT (p < 0.05). Ten volleyball players (13%) developed PT during follow-up. No knee kinematic risk factors for PT were identified. Increased concentric knee joint work during all jump-landing tasks (block jump Hazard Ratio (HR) = 1.323, p = 0.012; spike jump HR = 1.200, p = 0.033; drop vertical jump HR = 1.240, p = 0.036) and increased eccentric knee joint work during the block jump (HR = 1.246, p = 0.035) were predictive parameters to develop PT. The results of this study suggest that knee joint work is an important measure in the prevention of PT, whereas the evaluation of joint kinematics is not sensitive enough to predict this overuse injury. Further research is needed to investigate if adaptation of the defined risk factors could prevent PT.